Electrodeposited Fe and Fe–Au nanowires as MRI contrast agents. Issue 85 (6th October 2016) - Shore, Daniel; Pailloux, Sylvie L.; Zhang, Jinjin; Gage, Thomas; Flannigan, David J.; Garwood, Michael; Pierre, Valérie C.; Stadler, Bethanie J. H.
Abstract : T 2 -Weighted images (9.4 T, 25 °C) of electrodeposited Fe and Fe–Au nanowires, various concentrations, coated with PEG. Abstract : Electrodeposited Fe and Fe–Au nanowires were studied for potential as MRI contrast agents, especially for T 2 -weighted imaging. Transverse relaxivities up to r 2 = 77.1 mM Fe −1 s −1 (at 1.5 T) were achieved when Fe–Au nanowires were coated with thiol and carboxylic acid functionalized poly(ethyleneglycol). T 2 -Weighted images (9 T) verified successful contrast.